Real-life Effectiveness of Afatinib Versus Gefitinib in Patients With Non-small-cell Lung Cancer: A Czech Multicentre Study - Svaton, Martin; Bratova, Monika; Fischer, Ondrej; Krejci, Jana; Koubkova, Leona; Cernovska, Marketa; Hrnciarik, Michal; Zemanova, Milada; Coupkova, Helena; Porzer, Bedrich; Dolezal, Daniel; Tuzova, Tana; et al. (Anticancer research, 2021)
BACKGROUND/AIM: We investigated efficacy differences for afatinib versus gefitinib in non-small-cell lung cancer (NSCLC) according to epidermal growth factor receptor (EGFR) mutations. PATIENTS AND METHODS: We retrospectively analysed data for 343 patients with NSCLC with performance status 1 having EGFR mutations treated with gefitinib or afatinib. Overall response rate (ORR) was tested by Fisher's exact test. Overall (OS) and progression-free (PFS) survival were estimated by Kaplan-Meier method. RESULTS: ORR did not differ in any group or subgroup. Among all patients, we observed significantly longer PFS for those treated with afatinib vs. gefitinib (median 13.4 vs. 9.5 months, p=0.026), but only a nonsignificant trend was observed for OS. We showed nonsignificant trends of better PFS and OS using afatinib for exon 19 deletion and L858R subgroups. We observed no significant PFS differences for other EGFR mutations but a nonsignificant trend towards better OS for those treated with afatinib. CONCLUSION: Afatinib led to longer PFS for patients with common EGFR mutations but not for those with rare mutations.
Keywords: senioři; Disease Progression; senioři nad 80 let; NSCLC; Retrospective Studies; progrese nemoci; gefitinib; výsledek terapie; Česká republika; Middle Aged; mužské pohlaví; Gefitinib; ErbB Receptors; nádory plic; mutace; Adult; mladý dospělý; Czech Republic; real world data; Aged, 80 and over; Afatinib; Young Adult; nemalobuněčný karcinom plic; ženské pohlaví; Mutation; retrospektivní studie; Humans; Carcinoma, Non-Small-Cell Lung; erbB receptory; lidé středního věku; afatinib; dospělí; Female; Aged; Treatment Outcome; Lung Neoplasms; lidé; Male